2021
DOI: 10.34172/aim.2021.103
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic Electrocardiography Findings of COVID-19 Patients

Abstract: Background: Determining a relationship between coronavirus disease 2019 (COVID-19) and the ECG findings of the patients with this disease can assist in early diagnosis and patient management based on these findings. This study aimed to investigate whether COVID-19 patients had characteristic ECG findings in the acute period. Methods: A total of 124 patients were divided into two groups as those diagnosed with COVID-19 and controls. The ECGs of these patients were evaluated in terms of rate, rhythm, presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…This may be due to the fact that in our institution, we prescribed HCQ/AZT combination regimen during a limited period (04/06/2020 to 04/16/2020) in a limited number of patients (n = 13) and ECG was not systematically performed. Other ECG abnormalities that we describe in our study are consistent with the literature ( 26 28 , 33 ). Interestingly, we found that left bundle branch block, S1Q3 pattern and repolarization abnormalities were independently associated with death in cases of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This may be due to the fact that in our institution, we prescribed HCQ/AZT combination regimen during a limited period (04/06/2020 to 04/16/2020) in a limited number of patients (n = 13) and ECG was not systematically performed. Other ECG abnormalities that we describe in our study are consistent with the literature ( 26 28 , 33 ). Interestingly, we found that left bundle branch block, S1Q3 pattern and repolarization abnormalities were independently associated with death in cases of COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…It is now well-known that ECG is modified by systemic inflammation, which may be consecutive to COVID infection or any of its complications ( 6 , 8 ). In previous studies, an abnormal ECG was observed in between 47 and 93% of COVID-19 patients ( 23 , 24 , 26 28 ). In our study, 71.4% of patients presented with ECG abnormalities: 68.7% in patients admitted in medical wards and 79.3% in ICU patients.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…SARS-CoV-2, the virus that causes the coronavirus disease 2019 (COVID-19) pandemic, can invade both respiratory system and other vital organs such as the heart [58] . Early studies have shown multiple cardiovascular alterations in COVID-19 patients [59,60] , allowing the use of ECG for COVID-19 diagnosis. Rahman et al [61] adopted the transfer learning strategy and used ECG images to automatically diagnose COVID-19 and other cardiac diseases.…”
Section: Epidemic Prevention and Controlmentioning
confidence: 99%